2019
DOI: 10.1038/s41390-019-0697-9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal encephalopathy therapy optimization for better neuroprotection with inhalation of CO2: the HENRIC feasibility and safety trial

Abstract: BACKGROUND: There is an association between hypocapnia and adverse neurodevelopmental outcome in infants with neonatal encephalopathy (NE). Our aim was to test the safety and feasibility of 5% CO 2 and 95% air inhalation to correct hypocapnia in mechanically ventilated infants with NE undergoing therapeutic hypothermia. METHODS: Ten infants were assigned to this open-label, single-center trial. The gas mixture of 5% CO 2 and 95% air was administered through patient circuits if the temperature-corrected PCO 2 ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Although NE infants with cumulative pCO 2 above the 50th percentile were more likely to have seizures and needed more time to achieve spontaneous respiration, only the time to spontaneous respiration of more than 10 min had a significant association with adverse outcomes. 41 Hansen et al 39 retrospectively studied 23 neonates with moderate to severe NE treated with 72 h of hypothermia and it was found that those from the group with adverse neurodevelopmental outcomes had greater PaCO 2 variability than those from the group with favourable neurodevelopmental outcomes. The hypoxic-ischaemic encephalopathy therapy optimization in neonates for better neuroprotection with inhaled CO 2 (HENRIC) study, which involved 10 term infants, recently demonstrated that inhaled 5% CO 2 was feasible and safe for correcting hypocarbia in NE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although NE infants with cumulative pCO 2 above the 50th percentile were more likely to have seizures and needed more time to achieve spontaneous respiration, only the time to spontaneous respiration of more than 10 min had a significant association with adverse outcomes. 41 Hansen et al 39 retrospectively studied 23 neonates with moderate to severe NE treated with 72 h of hypothermia and it was found that those from the group with adverse neurodevelopmental outcomes had greater PaCO 2 variability than those from the group with favourable neurodevelopmental outcomes. The hypoxic-ischaemic encephalopathy therapy optimization in neonates for better neuroprotection with inhaled CO 2 (HENRIC) study, which involved 10 term infants, recently demonstrated that inhaled 5% CO 2 was feasible and safe for correcting hypocarbia in NE.…”
Section: Resultsmentioning
confidence: 99%
“…The hypoxic-ischaemic encephalopathy therapy optimization in neonates for better neuroprotection with inhaled CO 2 (HENRIC) study, which involved 10 term infants, recently demonstrated that inhaled 5% CO 2 was feasible and safe for correcting hypocarbia in NE. 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocapnia may signal impaired restoration of cellular metabolism, predicting unfavorable outcome of resuscitation efforts [54]. Furthermore, hypocapnia can be a consequence of relative hyperventilation in response to metabolic acidosis, and prevention of hypocapnia by inhalation of 5%CO 2 may enhance the efficacy of TH [55]. The question of whether increased CO 2 levels (hypercapnia) maintained while establishing normoxia after asphyxia would convey neuroprotection has been proposed by a set of rat studies employing asphyxia very similar to the one employed in piglets in the present study [19,20,54].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, hypothermia, H 2 or graded restoration of normocapnia may target the activation of similar or even the same pro-survival mechanisms, and either one may activate these alone as efficiently as combined with each other. For instance, TH, CO 2 , and even H 2 are known to reduce neuronal excitability and metabolism, providing means for the occlusion of protective effects [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%